Nucleate boiling heat transfer of R-134a and R-134a/POE lubricant mixtures on smooth tube. (25th February 2021) - Kumar, Abhishek; Wang, Xiao-Zhe; Jaya Lakshmi, Boyapati; Hung, Jung-Tsung; Chen, Yu-Kai; Wang, Chi-Chuan
Highlights: Effect of POE lubricant (1–10%) on pool boiling heat transfer of R-134a refrigerant is investigated. Tests were performed with smooth tube with heat flux ranging from 10 to 90 kW/m 2 . The bubble size is reduced and the bubble density is increased appreciably with the oil addition. The heat transfer coefficient (HTC) may be increased or impaired depending on oil concentration. The influence of visocoity amid POEA-68 and POEA-170 on HTC is relatively small.. Abstract: The present study examines the influence of polyolester lubricant oil (POEA-68 and POEA-170) with R-134a on the nucleate pool boiling performance for a horizontal smooth tube. The heat flux ranges from 10 kW/m 2 to 90 kW/m 2 and the lubricant mass fraction varied from 1% to 10% at a saturation temperature of 10 °C, 0 °C and, −6 °C, respectively. The experimental results show that the heat transfer coefficient (HTC) of the pure refrigerant is increased with an increase in saturation temperature. But the presence of lubricant oil alters the HTC considerably. The addition of 3% POEA-68 lubricant shows the highest 29.3% HTC enhancement relative to pure refrigerant at a supplied heat flux of 70 kW/m 2 and at a saturation temperature of 0 °C. Whereas for R-134a/POEA-170 lubricant mixture at 3% of mass fraction, the highest enhancement in HTC was around 26% at a supplied heat flux of 70 kW/m 2 and −6 °C saturation temperature. The bubble size is reduced and the bubble density is increased appreciably with the addition of POE oil. It was observed that the HTC of lubricant-refrigerant mixtures differs appreciably with the variation of lubricant oi mass fraction ( ω ). The HTC first decreases at a very low mass fraction ( ω ≤ 1%), followed by an appreciable increase in the range of 1% ≤ ω  ≤ 3%, and finally reveals a continuous decline for the higher mass fraction. The dramatic decrease in HTC for lubricant-refrigerant mixture is associated with mass transfer resistance and a significant increase in surface tension.